Influencia de un programa didáctico, basado en la metacognición, en la comprensión lectora del inglés en estudiantes uinversitarios. - Acosta Jarama, Ena Miriam (2019)
ABSTRACT This research work aimed at demonstrating the influence of a didactic program, based on metacognition, on the three text representation levels of reading comprehension in English. The sample population consisted of 38 first-year students of the Human Medicine School at Universidad Nacional de Piura. The pre-experimental design of pre and posttest was used. The students were trained in metacognitive strategies for 56 hours to enhance their reading comprehension skills in both Spanish and English. A didactic guide was made containing texts focused on human health. For the inferential analysis, the Wilcoxon Test was used to contrast the hypothesis since the related data was obtained from the same group in the pretest and posttest. The Mc Nemar Test was also used to compare the percentage of correct answers in each item. The results led to the following conclusions: 1) The didactic program influenced significantly on the English reading comprehension of students, on the three text representation levels: superficial, semantic and inferential. 2) The level which was mainly influenced was the referential one.